Meaning of life as a resource for coping with psychological crisis: Comparisons of suicidal and non-suicidal patients - Kalashnikova, Olga; Leontiev, Dmitry; Rasskazova, Elena; Taranenko, Olga (Frontiers in Psychology, 2022)
Introduction. Meaning is an important psychological resource both in situations of accomplishment and in situations of ongoing adversity and psychological crisis. Meaning in life underlies the reasons for staying alive both in everyday and in critical circumstances, fulfilling a buffering function with respect to life adversities. Aim. The aim of the present study was to reveal the role of both meaningfulness, including specific sources of meaning and reasons for living, and meaninglessness (alienation) in patients suffering from profound crisis situations with or without suicidal intentions and behavior. Methods. The sample includes 148 patients (all Caucasian) who were referred to a crisis center in Moscow, Russia. 77 patients (54 females, mean age 32.00±11.98 years old) reported a current crisis situation in their life but denied suicidal thoughts or behavior while 71 patients (52 females, mean age 31.01±12.32 years old) reported suicidal ideations, self-harm or suicidal attempts. There were no gender or age differences between groups. Participants completed a number of measures of different aspects of meaning and meaninglessness, well-being, ill-being and psychological resources. For some patients (N=74), a clinical checklist was completed by their doctors assessing 28 various characteristics associated with the patient’s clinical status. Results and discussion. Meaningfulness and reasons for living were more helpful in distinguishing between reactions to profound crisis situations (suicidal intentions versus non-suicidal behavior) than were measures of well-being, ill-being, meaning crisis or personality resources. In both suicidal and non-suicidal crisis patients meaningfulness predicted more positive reasons for living. The relationship between meaningfulness and most reasons for living remained significant after controlling for clinically appraised suicidal “readiness”, acute stress and lack of social support. Self-transcendence was the major specific source of meaning predicting higher reasons for living after adjusting for general meaningfulness. Conclusion. The data cast some light on the psychological meaning of suicide. It follows that prevention efforts are to be focused not on eliminating the factors “pushing” one to suicidal behavior, but rather on supporting inner strengths conducive of a positive decision, to be. through enhancing meaningfulness and reasons for living.